Pancasila Sebagai Dasar Negara Dan Pandangan Hidup - Rahma Faujiah; Hafis Solihin; Gemantan Sakti (JPT : Jurnal Pendidikan Tematik, 2025)
This paper examines the position of Pancasila as the foundation of the state and the Indonesian nation's philosophy of life, and its relevance to the dynamics of modern life. As the foundation of the state, Pancasila serves as the source of all legal sources and the constitutional foundation that guides the administration of government. Philosophically, Pancasila is understood as a philosophical foundation containing the values of divinity, humanity, unity, democracy, and justice. As a philosophy of life, Pancasila serves as a moral, ethical, and spiritual guideline for Indonesian society in social, cultural, political, economic, and religious life. Through theoretical and analytical studies, this paper highlights the challenges of implementing Pancasila values amidst globalization, rapid technological developments, and the rise of individualism and disinformation that have the potential to erode national identity. The study's findings indicate that the practice of Pancasila still needs to be strengthened, particularly at the practical level, through character education, role models, consistent law enforcement, and a culture of tolerance and mutual cooperation. By optimizing the understanding and appreciation of Pancasila, the Indonesian nation can maintain unity while building a just, democratic, and civilized society. Keywords: Pancasila, state ideology, outlook on life, Pancasila values, implementation, national ideology, 1945 Constitution, morals and ethics, diversity, character education